Analisis Disparitas Pendapatan Per Kapita Antar Kecamatan dan Potensi Pertumbuhan Ekonomi Kecamatan di Kabupaten Karangasem - Amrillah, Amrillah Amrillah; Yasa, I Nyoman Mahaendra (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 2, No. 4, April 2013 (pp. 173-225), 2013)
Karangasem regency has not been able to make optimal use of regional autonomy granted to increase the economic  growth and equitable in each district. In the BPS’s list shows Karangasem regency is a district that has the lowest per capita income in the period of the research with a high level of inequality. This research is aims to determine the level of GRDP per capita disparities between districts and determine the strategic economic sectors and the potential to be developed in their respective districts in Karangasem. The analysis is used for research purposes is the analysis of regional income disparities using index williamson, location quotient (LQ), shift share and typology klassen. The result analysis shows, there is disparity among districts in the regency of Karangasem with growing tendency annually indicated by the value of the index williamson from 2005 to 2010, which continued to rise. Strategic sectors of the economy and the potential to be developed to support economic growth in each district are as follows: (1) Rendang is the electricity, gas and water supply; finance, leasing, and business services, and the services sector. (2) Sidemen are the financial sector, leasing, and business services; sectors of electricity, gas and water supply, and the services sector. (3) Manggis is a sector of building / construction; transport and communication, trade, hotels and restaurants, and the electricity, gas, and water. (4) Karangasem is the electricity, gas and water supply; services sector, and sectors of building / construction. (5) Abang is the financial, leasing and business services; sectors of agriculture, mining and quarrying; electricity, gas, and water utilities; sectors of building / construction, and services sectors. (6) Bebandem is the mining and quarrying; electricity, gas, and water utilities; sectors of building / construction; transport and communication; finance, leasing, and business services, and the services sector. (7) Selat is the mining and quarrying sector, and financial sector, leasing, and corporate services. (8) Kubu is the mining and quarrying; finance, leasing, and business services, and agriculture.
Keywords: disparities , potential sectors , economic growth